THE APPLICATION OF A TACTICAL LEARNING MODEL TO IMPROVE GAME UNDERSTANDING IN FOOTBALL AMONG GRADE VIII STUDENTS AT SMP NEGERI 1 BADAR - Irvan Saputra; Fakhrur Rizal; Orbit Irwansyah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study investigates the effectiveness of the Tactical Games Model (TGM), an approach rooted in the Teaching Games for Understanding (TGfU) pedagogy, in enhancing game understanding in football among junior high school students. A quasi-experimental design with a pretest-posttest control group was employed. A sample of 60 Grade VIII students from SMP Negeri 1 Badar was divided into two groups: an experimental group (n=30) that received instruction via the tactical model, and a control group (n=30) that underwent conventional, technique-focused training. Game understanding was quantitatively assessed using the Game Performance Assessment Instrument (GPAI), which measures components such as decision-making, skill execution, and support in game-like situations. The results from paired sample t-tests indicated a statistically significant improvement in game understanding from pretest to posttest for both groups (p < .05). However, the experimental group demonstrated a substantially greater improvement, with an average gain score of 17.5 points, compared to the control group's average gain of 6.5 points. This significant difference in gain scores confirms the superior efficacy of the tactical learning model. The study concludes that the tactical approach, which embeds technical skill development within a contextual, game-centered learning environment, is significantly more effective than the traditional technical model in fostering a deeper and more applicable understanding of football among students. The findings advocate for a pedagogical shift in physical education towards models that prioritize tactical awareness and decision-making.